Lifetime Carcinogenic Risk Proportions from Inhalation Exposures in Industrial and Non-Industrial Regions - Jiřík, Vítězslav; Tomášek, Ladislav; Fojtíková, Ivana; Janoš, Tomáš; Stanovská, Markéta; Guňková, Pavlína; Dalecká, Andrea; Vrtková, Adéla; Šrám, Radim J (International journal of environmental research and public health, 2021)
The aim of this work was to estimate the share of selected significant risk factors for respiratory cancer in the overall incidence of this disease and their comparison in two environmentally different burdened regions. A combination of a longitudinal cross-sectional population study with a US EPA health risk assessment methodology was used. The result of this procedure is the expression of lifelong carcinogenic risks and their contribution in the overall incidence of the disease. Compared to exposures to benzo[a]pyrene in the air and fibrogenic dust in the working air, several orders of magnitude higher share of the total incidence of respiratory cancer was found in radon exposures, for women 60% in the industrial area, respectively 100% in the non-industrial area, for men 24%, respectively 15%. The share of risks in workers exposed to fibrogenic dust was found to be 0.35% in the industrial area. For benzo[a]pyrene, the share of risks was below 1% and the share of other risk factors was in the monitored areas was up to 85%. The most significant share in the development of respiratory cancer in both monitored areas is represented by radon for women and other risk factors for men.
Keywords: hodnocení rizik; Female; ženské pohlaví; průřezové studie; lidé; Occupational Exposure; lifetime cancer risk; Industry; Carcinogens; Risk Assessment; inhalační expozice; benzo[a]pyrene; radon; Cross-Sectional Studies; Male; průmysl; prach; karcinogeny; pracovní expozice; lung cancer; Dust; occupational exposure; mužské pohlaví; Inhalation Exposure; Humans